Compensation for dystrophin-deficiency: ADAM12 overexpression in skeletal muscle results in increased alpha 7 integrin, utrophin and associated glycoproteins. - Moghadaszadeh, B; Albrechtsen, R; Guo, LT; Zaik, M; Kawaguchi, N; Borup, R; Kronqvist, P; Schroder, H; Davies, K; Voit, T; Nielsen, F; Engvall, E; et al. (2003)
Mouse models for genetic diseases are among the most powerful tools available for developing and testing new treatment strategies. ADAM12 is a disintegrin and metalloprotease, previously demonstrated to significantly alleviate the pathology of mdx mice, a model for Duchenne muscular dystrophy in humans. More specifically ADAM12 appeared to prevent muscle cell necrosis in the mdx mice as evidenced by morphological analysis and by the reduced levels of serum creatine kinase. In the present study we demonstrated that ADAM12 may compensate for the dystrophin deficiency in mdx mice by increasing the expression and redistribution of several components of the muscle cell-adhesion complexes. First, we analyzed transgenic mice that overexpress ADAM12 and found mild myopathic changes and accelerated regeneration following acute injury. We then analyzed changes in gene-expression profiles in mdx/ADAM12 transgenic mice compared with their littermate controls and found only a few genes with an expression change greater than 2-fold between mdx/ADAM12 and mdx. The small changes in gene expression were unexpected, considering the marked improvement of the mdx pathology when ADAM12 is overexpressed, and suggested that significant changes in mdx/ADAM12 muscle might occur post-transcriptionally. Indeed, by immunostaining and immunoblotting we found an approximately 2-fold increase in expression, and distinct extrasynaptic localization, of alpha 7B integrin and utrophin, the functional homolog of dystrophin. The expression of the dystrophin-associated glycoproteins was also increased. In conclusion, these results demonstrate a novel way to alleviate dystrophin deficiency in mice, and may stimulate the development of new approaches to compensate for dystrophin deficiency in animals and humans.